NON-FERMENTING GRAM-NEGATIVE BACTERIA IN BLOOD CULTURE: A MENACE IN INTENSIVE CARE UNIT SETTINGS - DHARMENDER KUMAR; RUMANA FAROOQ MIR; HARIT KUMAR; NARINDER KAUR; ROSY BALA; JYOTI CHAUHAN (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: To know the prevalence of NFGNB isolated from blood culture specimens and their antibiotic sensitivity pattern in intensive care units. Methods: A total of 3393 blood samples during 1 year were received from patients admitted in various ICUs. 5–7 mL blood was aseptically collected and added in BACTEC bottles and then subsequently incubated in BD BACTECTM (FX40) fluorescent series instrument for up to 5 days. After incubation period, positive samples were processed for gram stain and subsequently sub-cultured on blood agar and MacConkey agar. These plates were incubated at 37°C for 24 h. Further identification and antimicrobial susceptibility testing of NFGNB were carried out by Vitek-2 Compact (Biomerieux India) as per the standard operating procedures. Results: Out of 3393 samples 696 samples showed growth, out of which 96 (13.79%) were Gram-positive cocci, 36 (5.17%) were Candida spp., and 564 (81.03%) were Gram-negative bacilli (GNB). Among 564 GNB, 453(80.31%) were lactose fermenter and 111 (19.68%) were non-lactose fermenters. One (0.53%) isolate of Aeromonas hydrophila was excluded from this study. Among 110 NFGNB, Acinetobacter baumannii complex (41.66%) was the most predominant followed by Pseudomonas aeruginosa (32.72%). Amikacin was the most sensitive drug for all the NFGNB isolates followed by Piperacillin/Tazobactam. Stenotrophomonas maltophilia showed excellent susceptibility to minocycline (83.33%) followed by ceftazidime (66.66%). Burkholderia cepacia showed good susceptibility to Trimethoprim/Sulfamethoxazole. Conclusion: Increasing antimicrobial resistance in NFGNB and their intrinsic or acquired resistance to many antibiotics makes them more lethal. It is therefore recommended to have quality guidelines on the “rational use of antibiotics” which need to be implemented strictly